MANAJEMEN PERSALINAN PERABDOMINAL PADA GAMELLI DI RS BAYANGKHARA PADANG - Primadella Fegita (Nusantara Hasana Journal, 2023)
A twin pregnancy or multiple pregnancy is a pregnancy with two or more fetuses. Multiple pregnancies can be multiple pregnancies or gemelli (2 fetuses), triplet (3 fetuses), quarrulet (4 fetuses), quintuplet (5 fetuses) and so on. Multiple pregnancies occur if two or more ova are released and fertilized (dizygotic) or if one fertilized ovum divides early to form two embryos (monozygotic). A twin pregnancy is one pregnancy with two or more fetuses. The increase in the number of twin births is mainly due to the increasing use of assisted reproductive techniques, including in vitro fertilization (IVF). Pregnancy and childbirth carry risks for the fetus. The danger to the mother is not so great, but women with multiple pregnancies require special supervision and attention when a satisfactory outcome is desired for both mother and fetus. The more the number of fetuses conceived by the mother, the higher the risk that will be borne by the mother. Therefore, the authors would like to present a case regarding the management of perabdominam delivery in pregnancies of patients G1P0A0H0 preterm gravid 33-34 weeks + PEB.